Reliability modelling of dispensing processes in community pharmacy - Naybour, M.; Remenyte-Prescott, Rasa; Boyd, Matthew (2018)
Studies of error rates in community pharmacies have reported error rates of between 0.014% and 3.3% per item dispensed. This suggests up to 36 million items per year may contain errors in England. In addition, literature shows that patient satisfaction with services is directly related to waiting times. There is a need for a method to model pharmacy efficiency balancing safety and waiting times, ensuring that the reliability of the dispensing process is not compromised. In this paper a Coloured Petri Net (CPN) approach is proposed for analysing reliability and efficiency of community pharmacy. A pharmacy team work to complete dispensing and non-dispensing tasks, where non-dispensing tasks require staff to be temporarily removed from the dispensing process. The proposed approach is useful to investigate what affects the error rates and long waiting times, and provides modelling-based evidence to decision makers, looking to optimise staffing levels and improve the reliability of dispensing.